The Rise of Nerd Politics: Digital Activism and Political Change - John Postill (2018)
The irruption of WikiLeaks, Anonymous, Snowden and other tech-savvy actors onto the global political stage raises urgent questions about the impact of digital activism on political systems around the world. The Rise of Nerd Politics is an anthropological exploration of the role that such actors play in sparking and managing new processes of political change in the digital age.Drawing from long-term ethnographic research in Spain and Indonesia - as well as case studies from the United States, Iceland, Tunisia, Taiwan, Brazil and elsewhere - Postill tracks the rise of techno-political 'nerds' as a new class of political brokers with growing influence. The book identifies and explores four domains of 'nerd politics' that have dramatically expanded since 2010: data activism, digital rights, social protest and formal politics. A lively and engaging intervention at the conjuncture of anthropology, media studies and sociology, The Rise of Nerd Politics offers a pertinent reflection on the future of political change in the digital age. -- from publisher's website.